Writing biographies on female religious leaders: Helena Petrovna Blavatsky and Annie Besant between a “search for truth” and “self-fulfillment” - Albrecht, Jessica A.; Perovic, Jovana (delta-Philosophie Heidelberg e.V., 2023)
Helena Petrovna Blavasky (1831-1891) and Annie Besant (1847-1933) as two influential leaders of the Theosophical Society can be seen as remarkable women of their time. Not only as religious leaders, they transgressed the gender roles of their time and – in different degrees – engaged with their contemporary feminist discourses. However, as this article shows, biographies on both have yet failed a greater analysis of gendered aspects as well as situating them in the feminist contexts of their time. Instead, their biographies including any obscure aspects of gender are explained by situating them in relation to the Theosophical Society only. However, one such analysis of gender is useful for biographies, in particular in these case studies. Consequently, as we illustrate in these examples, we maintain that gender has to be an integral part of biographies.